2014
DOI: 10.1128/aem.04016-13
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Abundance and Diversity of Mobile Genetic Elements after the Introduction of Diverse Pesticides into an On-Farm Biopurification System over the Course of a Year

Abstract: f Biopurification systems (BPS) are used on farms to control pollution by treating pesticide-contaminated water. It is assumed that mobile genetic elements (MGEs) carrying genes coding for enzymes involved in degradation might contribute to the degradation of pesticides. Therefore, the composition and shifts of MGEs, in particular, of IncP-1 plasmids carried by BPS bacterial communities exposed to various pesticides, were monitored over the course of an agricultural season. PCR amplification of total community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 45 publications
(49 reference statements)
3
51
0
Order By: Relevance
“…The tetracycline ARGs tetW and tetM belong to the class of ribosomal protection resistance genes [33]. The sulfonamide ARG sulI is an indicator of both horizontal gene transfer and multiple antibiotic resistance, because it is generally encoded within a class 1 integron on conjugative plasmids containing other resistance genes; the sulfonamide ARG sulII is usually encoded on small nonconjugative plasmids or large transmissible multiresistance plasmids [8]. Besides harboring ARGs, several mobile genetic elements (MGEs) are also assumed to be vital for the adaptation and biodegradation of organic pollutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetracycline ARGs tetW and tetM belong to the class of ribosomal protection resistance genes [33]. The sulfonamide ARG sulI is an indicator of both horizontal gene transfer and multiple antibiotic resistance, because it is generally encoded within a class 1 integron on conjugative plasmids containing other resistance genes; the sulfonamide ARG sulII is usually encoded on small nonconjugative plasmids or large transmissible multiresistance plasmids [8]. Besides harboring ARGs, several mobile genetic elements (MGEs) are also assumed to be vital for the adaptation and biodegradation of organic pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Among these efforts, bioremediation with degrading bacteria and surfactant application proved to be one of the most efficient ways for the simultaneous removal of mixed pollutants from soil [5,6]. However, there is emerging evidence indicating that the co-existence of persistent organic pollutants with antibiotics or antibiotic resistance genes (ARGs) is a concern, which is not yet fully understood [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Several previous studies reported a positive effect of increased PAH content on the upregulation of bacterial efflux pumps responsible for both antibiotic resistance and PAH efflux (Bugg et al, 2000). Dealtry et al (2014) detected a clear enhancement in the relative abundance of bacteria carrying IncP-1b plasmids accompanied with the increasing concentrations of various pesticides, suggesting a role of these OPs in the stimulation of the MGEs expression. Yet several other observations suggested no clear correlation between OPs and/or antibiotic contents and the abundance of antibiotic resistant bacteria or ARGs in soil (Negreanu et al, 2012;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…IncP-1, intI1 and intI2) might involve in the organic pollutants degradation (Dealtry et al, 2014), it is still not clear whether there is any clear correlation between OP content and ARG abundance. Therefore, we attempted to align the correlation analysis with the total/ bioaccessible concentrations of OPs and the relative abundance of ARGs.…”
Section: Relationship Between Op Concentration and Arg Abundancementioning
confidence: 99%
“…These plasmids and transposons include multiresistance and heavy metal resistance plasmids as, for example reported for qacA and qacB genes, respectively (Russell 1997), but they were also associated with degradative pathways in a pesticide polluted environment (Dealtry et al 2014). Class 1 integrons including qac genes are frequently found on IncP-1 plasmids which are broad host range plasmids widely distributed in the environment such as soil, manure, sludge, digestates and river sediments (Jechalke et al 2015;Smalla et al 2006;Zhang et al 2011b;Heuer et al 2012;Popowska and Krawczyk-Balska 2013;Wolters et al 2015).…”
Section: Role Of Qaacs In the Selection Of Antibiotic Resistancementioning
confidence: 98%